Faktor-Faktor Pasangan Usia Subur dalam Perilaku Keikutsertaan IVA di Wilayah Kerja Puskesmas Puding Kabupaten Muaro Jambi - Yesi Bustina; Silvia Mariana (Universitas Baiturrahim, 2023)
According to the World Health Organization (WHO) in 2018 cervical cancer ranks fourth in women, an estimated 570,000 women are diagnosed with cervical cancer worldwide and around 311,000 women die from the disease. One of the government's efforts in early detection of cervical cancer is the IVA examination. One of the government's efforts in early detection of cervical cancer is the IVA examination. This research is an analytical study with a cross-sectional design. The population in this study was 354 PUS with family planning. The sampling technique used Accidental Sampling, namely 108 samples, where the research was carried out by filling out questionnaires, analyzed using univariate and bivariate analysis. to determine the relationship between the independent variable and the dependent variable. The results showed that 77.8% of the respondents had never had an IVA checked, 54.6% had less knowledge, 50.0% of the respondents did not have a fixed income, 61.1% of the respondents received less support from their husbands, as many as 56.6% of the majority of respondents have secondary education. The conclusion is that the results of bivariate analysis show that there is a significant relationship between knowledge (p=0.000) and the behavior of IVF examination, while education (p=0.670), income/economy (p=0.312) husband's support (p=1.000) do not have a significant relationship with behavior VIA examination